2019
DOI: 10.14527/pegegog.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of grade level and gender-based science achievement gaps in schools with different science achievement levels

Abstract: Science achievement gap between fifth, sixth, and eighth grades and boys and girls in low and high performing schools were under investigation in the present study. In accordance with this purpose, three schools were selected to represent high performing schools and two schools were selected to represent low achieving schools for their performance on a nationwide exam. A total of 612 fifth, 816 sixth, and 604 eighth grade students in high achieving schools and 231 fifth, 364 sixth, and 328 eighth grade student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
1
3
0
3
Order By: Relevance
“…The finding that genderbased attitude difference is observed only in SHSA is similar to the result that gender-based science achievement difference is seen in certain parts of the science achievement distribution which is reported by Gevrek and Seiberlich (2014). In addition, Acar (2020) found that gender-based achievement gap which is in favor of girls increased as the grade level increased in SHSA. According to these results, it can be inferred that gender-based attitudes towards science and science achievement differences are more apparent in SHSA.…”
Section: Discussion and Conclusion Related To Gendersupporting
confidence: 80%
See 3 more Smart Citations
“…The finding that genderbased attitude difference is observed only in SHSA is similar to the result that gender-based science achievement difference is seen in certain parts of the science achievement distribution which is reported by Gevrek and Seiberlich (2014). In addition, Acar (2020) found that gender-based achievement gap which is in favor of girls increased as the grade level increased in SHSA. According to these results, it can be inferred that gender-based attitudes towards science and science achievement differences are more apparent in SHSA.…”
Section: Discussion and Conclusion Related To Gendersupporting
confidence: 80%
“…On the other hand, it is a desired situation that students enhance science outside school scores as their grade level increases in SHSA. Despite the decrease in science achievement as the grade level increases in SHSA (Acar, 2020), the increase in science outside school scores is a finding that needs interpretation. We think that high SES of students' parents in SHSA may trigger this result.…”
Section: Discussion and Conclusion Related To Grade Levelmentioning
confidence: 94%
See 2 more Smart Citations
“…The results and discussions will be explained in five sub-sections. In the first section, descriptive studies of questionnaire items will be given, Access Difference among Online In the research study delivered by with respect to these factors, earlier studies (Acar, 2020;Ahmed, 2007;Anderson, et.al, 2007;Bhanji, 2008;Clarke et al, 2008;Gregory, et.al, 2010;Goldhaber, et. al, 2019,).…”
Section: Findings and Discussionmentioning
confidence: 99%